Scanning electron microscopic investigation of changes in the dentogingival area during experimental gingivitis - Walsh, T F; Walmsley, A D; Carrotte, P V (Journal of clinical periodontology, 1991)
The purpose of this study was to investigate the changes that occur in the dentogingival area during experimental gingivitis using a replication technique and scanning electron microscopy (SEM). The upper 1st premolars of 20 subjects were examined prior to plaque accumulation, after plaque had become clinically visible and after 3 weeks plaque accumulation. 3 distinct zones were examined: the tooth surface and its integuments, the gingival crevice and the oral gingiva. Surface features such as perichymata, pits, depressions and cracks were rapidly covered by plaque deposits. These had a raised globular surface with occasional embedded desquamated epithelial cells. Raised plaque colonies were frequently seen by the end of the study. Initially, the gingival crevice presented a layered undulating appearance. With plaque accumulation many desquamating epithelial cells were seen and variations occurred in the width of the crevice. These changes were mirrored in the oral gingiva. The junctional epithelium was initially smooth with occasional pores and emigrating leucocytes. As plaque accumulated, the presence of pores and leucocytes increased and considerable disruption by desquamating epithelial cells was noted. No subject proved resistant to the influence of plaque-induced changes.